AD‐ and PSP‐specific brain‐derived tau oligomers engage synapses with different dynamic. (1st February 2022) - Marcatti, Michela; Fracassi, Anna; Bhatt, Nemil; Natarajan, Chandramouli; Krishnan, Balaji; Kayed, Rakez; Taglialatela, Giulio
Abstract: Background: Alzheimer's Disease (AD) is characterized by gradual cognitive decline driven by the targeting of synapses by small oligomers of both Aβ (AβO) and tau (TauO), which results in synaptic dysfunction that ultimately underscores disease progression. Indeed, there is ample consensus that targeting oligomer binding to synapses would be an effective therapeutic concept for AD. However, recent failures of clinical trials of Aβ‐directed therapeutics suggest reduced effectiveness of targeting Ab in clinically‐manifest AD, redirecting attention onto TauO that are known to increase later in the disease timeline. In support of this vision, here we show that recombinant TauO, human brain derived tau oligomers (BDTO) and AβO target synapses with different dynamics. Method: We used recombinant AβO and TauO as well as BDTO from AD (BDTO‐AD), and from Progressive Supranuclear Palsy (BDTO‐PSP). Analyses of flow‐cytometry, western blot, immunofluorescence, and proteinase K digestion were performed to study the binding dynamic of the oligomers onto synaptosomes isolated from human and mouse frontal cortex and hippocampus. The synaptic dysfunction was measured by FASS‐LTP assay. Result: We found that TauO overcome AβO, becoming the prevailing species associated with the synapses. On the other hand, AβO are ineffective in competing TauO off the synapses, and at higher concentration AbO increase TauO binding to the synaptosomes. Consistent with these observations, analyses of FASS‐LTP show that the suppression of long‐term potentiation by TauO is not affected by the concomitant presence of AβO. Pre‐digestion of synaptosomes with proteinase K abolishes the ability of TauO to overcome AβO without affecting the increased synaptic recruitment of TauO by high levels of AβO, suggesting that the former phenomenon necessitates of a protein substrate whereas the latter does not. Furthermore, we observed different synaptic engagement and internalization profiles among the analyzed BDTOs, suggesting different synaptic toxicity of TauO across the tauopathies spectrum. Conclusion: Our results suggest that at the advanced stages of AD, when tau levels increase, TauO become the main synaptototoxic species and likely an effective therapeutic target. Furthermore, subtle disease‐specific differences in the dynamic of BDTOs engagement of synapses may underscore different clinical presentations among the tauopathy spectrum.